Peridinium quinquecorne var. trispiniferum var. nov. (Dinophyceae) from a brackish environment - José Antolín Aké Castillo; Gabriela Vázquez Hurtado (Acta Botánica Mexicana, 2011)
Peridinium quinquecorne is a marine dino agellate that bears four characteristic thick spines on the hypotheca. Some specimens, which characteristics of shape, number and arrangement of plates matched those of this species, were found in phytoplankton samples collected at the Sontecomapan coastal lagoon, Mexico, in 1999, 2001, 2003 and 2007. However, the organisms collected bore three spines on the hypotheca instead of four, as described for P. quinquecorne. The number of spines and their position on antapical plates were features consistently observed over at least a nine years period. From October 2002 to October 2003, we followed the dynamics of the phytoplankton community at the lagoon and this organism was found only in February and June, when salinity values were lower than 21? and temperatures higher than 24.5 °C. In February 2003, this organism reached high cell densities and became the dominant species in the phytoplankton community. Based on observations on the morphology of this dino agellate under the light and electron microscopes and its constant possession of only three spines, we propose the new variety name Peridinium quinquecorne var. trispiniferum for this taxon which caused a bloom in this tropical brackish system.